AB0844 Determinants of Returning to Work 12 Months After Total Joint Surgery: Differences Between Total Hip Arthroplasty and Total Knee Arthroplasty. (9th June 2015) - Leichtenberg, C.; Tilbury, C.; Kuijer, P.; Verdegaal, S.; Wolterbeek, R.; Nelissen, R.; Frings-Dresen, M.; Vliet Vlieland, T.
Abstract : Background: The majority of the patients undergoing Total Hip Arthroplasty (THA) or Total Knee Arthroplasty (TKA) returns to work postoperatively, but the absolute number of patients who do not return to work remains substantial. Little is known about factors limiting return to work 1, Objectives: To identify factors related to return to work after THA and TKA one year postoperatively. Methods: This one-year prospective cohort study included patients who were assessed preoperatively and one-year postoperatively, aged 65 years or younger, and who provided information on their work status. Assessments included a questionnaire and/or telephone interview on work status. The outcome of return to work was divided into full return to work vs. partial or no return to work. Potential determinants included the following preoperative characteristics: physical hip/knee-job demands (classified into light, medium or heavy), the amount of working hours a week, self-employement, sick leave duration, granted disability benefits, presence of work adaptions and expectations of returning to work. Logistic regression analyses were employed to determine factors associated partial/no return to work in all patients, controlling for type of surgery (THA or TKA). Results: Sixty-seven THA patients (mean age 56 years; SD 6.6, 33 females (49%)) and 56 TKA patients (mean age 56 years; SD 5.7, 31 females (55%)) were included. The mean amount of work hours a week preoperatively was 32 hours (SD 12.5) in THA patients and 31 hours (SD 12.3) in TKA patients. 53/67 THA patients (79%) and 40/56 TKA patients (71%) returned to work fully one-year post-operatively (same mean amount of work hours), whereas 5/67 THA patients (7%) and 7/56 TKA patients (13%) did not return to work at all and 9/67 THA patients (13%) and 9/56 TKA patients (16%) returned to work but less hours than preoperatively (mean decrease of work hours per week -17 hours (SD 11.5, P=0.002) in THA and -16 hours (SD 12.4, P=0.005) in TKA) The THA patients who returned to work partially or not had a lower educational level (P=0.006), were more often self-employed (P=0.009) and were more often absent from work due to hip complaints preoperatively than those fully returning to work (P=0.002). In the TKA group of patients there were no significant differences in characteristics of patients returning to work fully or not. In the multivariable logistic regression analyses, being self-employed (OR 7.4, 95%, CI 1.5-35.8), preoperative absence from work (OR 10.8, 95% CI 2.8-4.8) and working more hours preoperatively (OR 1.03, 95% CI 0.99-1.1) were factors significantly associated with partial/no return to work. Conclusions: Self-employment, working more hours and being absent from work preoperatively remained determinants for partial/no return to work after correcting for type of prothesis. These findings underline the need to study return to work after THA and TKA separately. References: C.Tilbury, et al., Return to work after total hip and knee arthroplasty: a systematic review. Rheumatology. (Oxford) 53(3), 512 (2014). Acknowledgements: This study was funded by the Anna Fonds/NOREF Disclosure of Interest: None declared